2019
DOI: 10.1080/21681376.2019.1663256
|View full text |Cite
|
Sign up to set email alerts
|

Economic drivers in cross-border regional innovation systems

Abstract: This paper investigates the main forces driving economic integration in cross-border regions (CBRs). Drawing on the proximity framework, it contends that all four forms of proximity need to be stressed in cross-border regional economic integration discourses. The paper is based on a comparison of two cross-border regional contexts in North America, which have been investigated using a survey and semi-structured interviews. Based upon the data collected, the two case studies shed a light on cognitive proximity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…However, over the years, the ‘Maquiladora program’ has improved the socio-economic status of local people and promoted the training of the local workforce improving the availability of knowledge workers, which has been important for cross-border knowledge flows and innovation cooperation. This has helped to leverage innovation in the CBR, as companies in Tijuana have also been increasingly developing their production processes in collaboration with partners from the US side of the border to match the needs of the high-tech industries present in San Diego (Cappellano and Rizzo, 2019). As a result, innovation cooperation across the border is slowly becoming more evenly balanced (Sandoval, 2020; Cappellano and Makkonen, 2020b).…”
Section: Case Study Analysismentioning
confidence: 99%
“…However, over the years, the ‘Maquiladora program’ has improved the socio-economic status of local people and promoted the training of the local workforce improving the availability of knowledge workers, which has been important for cross-border knowledge flows and innovation cooperation. This has helped to leverage innovation in the CBR, as companies in Tijuana have also been increasingly developing their production processes in collaboration with partners from the US side of the border to match the needs of the high-tech industries present in San Diego (Cappellano and Rizzo, 2019). As a result, innovation cooperation across the border is slowly becoming more evenly balanced (Sandoval, 2020; Cappellano and Makkonen, 2020b).…”
Section: Case Study Analysismentioning
confidence: 99%
“…Lundquist and Trippl (2011) propose three stages of proximity between border regions, based on the flow of collaborations: weakly integrated, semi-integrated and strongly integrated systems. Proximity is understood as the intensity of social links between actors in different territories, which allows them to be associated through the dynamics of scientific, innovative and productive collaboration (Capellano and Rizzo, 2019).…”
Section: Innovation Systems In the Context Of Regional Integrationmentioning
confidence: 99%
“…To inquire about this research problem, the innovation systems approach is applied to frontier spaces (Lundquist and Trippl, 2009; Capellano and Rizzo, 2019; Cappellano and Makkonen, 2019). This theoretical frame allows for the analysis of knowledge-based dynamics in multi-territorial spaces.…”
Section: Introductionmentioning
confidence: 99%
“…The geographical factors still prevail for certain areas of development, for example, the development of cross-regional innovation systems. F. Cappellano and A. Rizzo (2019) investigated several such systems and concluded that geographical factors dominated for them, while the institutional factors were the least important among the analyzed ones. A study conducted by Russian economists in 65 countries confirmed that climate determines the unique character of historically dominant institutions (Kirdina, 2016, p. 144).…”
Section: Theoretical Foundationmentioning
confidence: 99%